The role of endogenous thiamine produced via THIC in root nodule symbiosis in Lotus japonicus. (June 2019) - Yin, Yehu; Tian, Lu; Li, Xueliu; Huang, Mingchao; Liu, Leru; Wu, Pingzhi; Li, Meiru; Jiang, Huawu; Wu, Guojiang; Chen, Yaping
Highlights: The nodulation of ljthic is determined mainly by the photosynthesis from the shoot. Thiamine mediated by LjTHIC acts as an essential nutrient for rhizobial infection. Thiamine synthesized in roots contributes to nodule growth. Thiamine synthesized in the underground part cannot transport to the aerial part. Abstract: Thiamine is a pivotal primary metabolite which is indispensable to all organisms. Although its biosynthetic pathway has been well documented, the mechanism by which thiamine influences the legume-rhizobium symbiosis remains uncertain. Here, we used overexpressing transgenic plants, mutants and grafting experiments to investigate the roles played by thiamine in Lotus japonicus nodulation. ljthic mutants displayed lethal phenotypes and the defect could be overcome by supplementation of thiamine or by overexpression of LjTHIC. Reciprocal grafting between L. japonicus wild-type Gifu B-129 and ljthic showed that the photosynthetic products of the aerial part made a major contribution to overcoming the nodulation defect in ljthic . Overexpression of LjTHIC in Lotus japonicus ( OE-LjTHIC ) decreased shoot growth and increased the activity of the enzymes 2-oxoglutarate dehydrogenase and pyruvate dehydrogenase. OE-LjTHIC plants exhibited an increase in the number of infection threads and also developed more nodules, which were of smaller size but unchanged nitrogenase activity compared to the wildtype. Taken together, our results suggest that endogenous thiamine produced via LjTHIC acts as an essential nutrient provided by the host plant for rhizobial infection and nodule growth in the Lotus japonicus – rhizobium interaction.